The far-ultraviolet spectrum of NGC 4151 as observed with the Hopkins ultraviolet telescope on Astro-2 - ESPEY, BRIAN RUSSELL (American Astronomical Society, 1995)
We observed NGC 4151 on six separate occasions at intervals of 1 to 3 days using the Hopkins Ultraviolet Telescope during the flight of Astro-2 aboard the space shuttle Endeavour in 1995 March. The far-UV spectra cover the spectral range from the interstellar cutoff at 912 to 1840 A with a resolution of 2--4 A. The mean spectrum, representing 4752 s of integration time, has a signal-to-noise ratio of approximately 30, and it shows profound differences compared to that obtained during the flight of Astro-1 in 1990 December. The continuum, 5.3 x 10-13 erg cm-2 s-1 A-1 at 1455 A, is 5 times brighter, the brightest UV flux ever observed for NGC 4151. All high-ionization absorption lines have strengthened considerably---S VI lambda lambda 933, 945, C III lambda 977, O VI lambda lambda 1032, 1038, N V lambda lambda 1239, 1243, Si IV lambda lambda 1394, 1403, and C IV lambda lambda 1548, 1551. The Lyman series absorption lines have also increased in strength, with the bulk of the absorption requiring a neutral hydrogen column density of 5 x 1017 cm-2 covering only 78% of the UV source with an effective Doppler parameter of 350 km s-1. However, up to 5 x 1020 cm-2 of neutral hydrogen that fully covers the source could be present in gas with a thermal Doppler parameter of 20 km s-1. Single-zone photoionization models of warm absorbing gas are unable to account for both the X-ray absorbing material and the UV-absorbing gas, largely because of the wide range of ionization states present in the UV and the X-ray.
PUBLISHED
Keywords: Physics